LiDAR point clouds processing for large-scale cave mapping: a case study of the Majko dome in the Domica cave. Issue 2 (1st December 2022) - Šupinský, Jozef; Kaňuk, Ján; Nováková, Michaela; Hochmuth, Zdenko
ABSTRACT: The cave map, as a result of mapping in limited cave spaces, is a specific cartographic product characterized by a high degree of cartographic abstraction and subjectivity of the cave features. Over the last decade, remote sensing methods have been increasingly used in cave mapping. Specifically, the laser scanning technology can effectively record the vastly fragmented interior of the cave at a high level of detail. The presented paper demonstrates a methodology of making the high-scale cave map from LiDAR point clouds. The innovativeness of the presented approach is in the use of highly detailed model of a cave floor derived from a point cloud as a base data layer for identification of the cave features. The main benefit of the final cave map is in the diminution of the authoŕs subjective perception during the cave mapping resulting in the generalization of the cave spaces geometry and cave features.